Development and Theoretical Underpinnings of the PRIORITY Intervention: A Parenting Intervention to Prevent Disordered Eating in Children and Young People With Type 1 Diabetes - O’Donnell, Nicola R.; Satherley, Rose-Marie; John, Mary; Cooke, Debbie; Hale, Lucy S.; Stewart, Rose; Jones, Christina J. (Frontiers in Clinical Diabetes and Healthcare, 2022)
Abstract: Children and young people (CYP) with type 1 diabetes (T1D) are twice as likely to develop disordered eating (T1DE) and clinical eating disorders than those without. This has significant implications for physical and mental health, with some eating disorders associated with repeated diabetic ketoacidosis and higher HbA1c levels, both of which are life threatening. There is currently limited psychological support for CYP and families with T1D but increasingly, policy and practice are suggesting disordered eating in T1D may be effectively prevented through psychological intervention. We describe the development of a preventative psychological intervention for parents of CYP aged 11-14, with T1D. The intervention was informed by psychological theory, notably the Information Motivation Behaviour Skills model and Behaviour Change Technique Taxonomy. The intervention was co-developed with an expert advisory group of clinicians, and families with T1D. The manualised intervention includes two group workshops, and supplementary online materials. The intervention continues to evolve, with pilot findings suggesting the need for minor modifications to best align the intervention with routine care in NHS diabetes teams. Early detection and intervention are crucial in preventing T1DE, and it is hoped that the current intervention can contribute to improving the psychological and physical wellbeing of young people and families managing T1D.